Compact Inverse-Opal Electrode Using Non-Aggregated TiO2 Nanoparticles for Dye-Sensitized Solar Cells - Kwak, Eun Sik; Lee, Wonmok; Park, Nam-Gyu; Kim, Junkyung; Lee, Hyunjung (WILEY-V C H VERLAG GMBH, 2009)
Compact inverse-opal structures are constructed using non-aggregated TiO2 nanoparticles in a three-dimensional colloidal array template as the photoelectrode of a dye-sensitized solar cell. Organic-layer-coated titania nanoparticles show an enhanced infiltration and a compact the 3D array. Subsequent thermal decomposition to remove the organic template followed by impregnation with N-719 dye results in excellent inverse-opal photoelectrodes with a photo-conversion efficiency 3.47% under air mass 1.5 illumination. This colloidal-template approach using non-aggregated nanoparticles provides a simple and versatile way to produce efficient inverse-opal structures with the ability to control parameters such as cavity diameter and film thickness.
Keywords: POROUS MATERIALS; NANOTUBE-ARRAYS; ENHANCEMENT; FABRICATION; EFFICIENCY; CONVERSION; TEMPERATURE; PERFORMANCE; MORPHOLOGY; TRANSPORT